Género, migración y desarrollo. Entre Quito y Madrid, familias ecuatorianas y estrategias de movilidad social - Laura Oso Casas (Les Cahiers ALHIM)
The relation between migration and development has been a traditional line of research within the framework of literature addressing international migration issues. However, less work has been carried out into these issues from a gender-based perspective. This text considers the social mobility strategies of migrant households within the context of family strategies.  We study the behavioural strategies adopted by the various types of household (lone men or women, pioneering women, pioneering men, couples migrating together). We focus essentially on analysing the differences in investments made in financial, physical, human and social capital. Our analysis is based on the empirical material obtained from qualitative fieldwork (in-depth interviews) with the families of Ecuadorian migrants in the urban district of   Turubamba Bajo (Southern Quito) and Madrid.